2015
DOI: 10.1088/0951-7715/28/9/r89
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative buckling and the nonlinear mechanics of nematic semiflexible networks

Abstract: We review the nonlinear mechanics of cross-linked networks of stiff filaments with a quenched anisotropic (nematic) alignment. A combination of numerical simulations and analytic calculations shows that the broken rotational symmetry of the filament orientational distribution leads to a dramatic nonlinear softening of the network at very small strain (on the order of 0.1%). We argue that one can understand this softening in terms of Euler buckling, i.e. the loss of further load-carrying capacity in compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…The occurrences of fits with G'' < 0 indicates that the response of the system cannot be interpreted as being linear in the applied force. The presence of these nonlinear rheological effects of the intra-and interfibrillar cross-linking despite no detectable change in microstructure is consistent with nonlinear response of nematically aligned fiber networks (24) and will be a basis for further investigation.…”
Section: Discussionsupporting
confidence: 59%
“…The occurrences of fits with G'' < 0 indicates that the response of the system cannot be interpreted as being linear in the applied force. The presence of these nonlinear rheological effects of the intra-and interfibrillar cross-linking despite no detectable change in microstructure is consistent with nonlinear response of nematically aligned fiber networks (24) and will be a basis for further investigation.…”
Section: Discussionsupporting
confidence: 59%
“…3d which depicts a typical example at = 0.5%. The correspondence between strain stiffening and the increase in ∆ + is consistent with previous work, which found that similar non-linearity was required for asymmetric response to strain in simulated actin networks [12]. It therefore makes sense that the onset of strain stiffening and hysteresis occur at the same concentration.…”
Section: Dependence On Cross-linker Concentrationsupporting
confidence: 89%
“…While filament stretching dominates the mechanics of strain stiffening, filaments can also buckle under shear, creating a locally weakened region [11,12]. Changes in cross-linker concentration or filament orientation can influence the relative likelihood of shear-induced bending and stretching, impacting the mechanical response [12][13][14][15]. The physical properties of cross-linkers, such as their length and flexibility, also influences network structure and mechanics [16].…”
Section: Introductionmentioning
confidence: 99%
“…The buckling of semiflexible networks at small compressive strains thus induces a rich and complex mechanical behaviour of biopolymer systems and cellular materials (Foucard et al 2015). The buckling instability in swelling or shrinking hydrogels usually occurs in the poorly connected regions near the free surface in the form of wrinkles and propagate later within the drained network since a crosslinked microsctructure becomes unstable when the volume change is too large (Doi 2009).…”
Section: Discussionmentioning
confidence: 99%